Bike-buddies : entre todos nos podemos ayudar (2016)
BikeBuddies is a platform for BikeUsers, which arises in order to promote the creation of a community among them and thus combat part of the problems and challenges such as insecurity, accidents and conflicts that they have to face daily in their cities, to be able to enjoy one of your passions or simply transport yourself in an efficient and alternative, helping each other.